Corn husk as potential substrate for Pleurotus Florida cultivation - Tan, Shin Yee (Universiti Malaysia Sabah, 2018)
Corn husk was used as the alternative materials to replace sawdust in this study for commercial production of Pleurotus florida as the source of sawdust are getting limited. The objective of this study was to evaluate the growth and development and yield of white oyster mushroom (Pleurotus florida) using corn husk as substrate. Completely Randomised Design (CRD) was used in this study with total seven treatments. Substrate ratio with 100% sawdust was used as the control in the study. Mixture of 75% sawdust and 25% corn husk (T2), 67% sawdust and 33% corn husk (T3), 50% sawdust and 50% corn husk (T4), 33% sawdust and 67% corn husk (TS), 25% sawdust and 75% corn husk (T6) and 100% corn husk (T7) treatments with five replicates each were conducted. Results were analyzed by Statistical Analysis System (SAS), using one-way ANOVA procedure to test the significant difference at 5% significant level. Significance difference (p<0.05) were found in the mycelium running rate, duration of complete mycelium run, the time required for primordial initiation and duration from inoculation until harvest of first flush for the growth and development. While for the yield production, significance difference were found in the number of fruiting body, the number of effective fruiting body, fresh weight, dry weight and biological efficiency. However, there was no significant difference in time required for formation of fruiting body form primordial among the treatments in the growth and development. Diameter of cap, length of stem and moisture content also found no significant difference in the yield production. From this study, T3 (0.55±0.01 cm day-1), T4 (0.50±0.03 cm day-1), TS (0.51±0.03 cm day-1) and T6 (0.50±0.03 cm day-1) had the higher mycelium running rate than Tl but the shortest duration of complete mycelium run were found in Tl (33.20±0.49 days). The shortest time required for primordial formation of first flush was found in T7 (1.40±0.24 days). Furthermore, T7 (38.60±0.24 days) and T4 (38.60±0.24 days) had the shortest time required for the inoculation until first harvest. For the yield production, T7 had the highest number of effective fruiting body produced (17.8±1.28) and treatments with cornhusk mixture T7 (28.40±3.08), T6 (20.20±3.96), TS (23.00±1.93), T4 (22.00±3.99) and T3 (26.00±2.78) were found to have similar number of fruiting body produced. Highest fresh weight was harvested from T7 (108.90±10.48 g) and T3 (95.05±9.07 g) while the highest dry weight was obtained by T7 (7.14±0.60 g) as well. For the biological efficiency, T7 has the highest biological efficiency (51.37±4.95%) compared to other treatments. All the parameter measured were obtained for two flushes that produced along the period of cultivation. The findings suggested that there is potential to use com husk as substrate for P. florida cultivation, as substitute to the use of sawdust in current commercial practice.